Citri Reticulatae Pericarpium alleviates postmyocardial infarction heart failure by upregulating PPARγ expression. (30th March 2022) - Chen, Mengli; Zhu, Hongyan; Zhu, Qingqing; Wu, Xiaodong; Zhou, Yufei; Gao, Rongrong; Shi, Mengsha; Zhang, Ting; Yin, Ting; Zhang, Haifeng; Shang, Hongcai; Li, Xinli
Abstract: Heart failure after myocardial infarction (MI) is the leading cause of death worldwide. Citri Reticulatae Pericarpium (CRP) is a traditional Chinese herbal medicine that has been used in the clinic for centuries. In this study, we aimed to investigate the roles of CRP in cardiac remodelling and heart failure after MI, as well as the molecular mechanisms involved. Male C57BL/6 mice aged 8 weeks were subjected to coronary artery ligation to mimic the clinical situation in vivo. Echocardiography was used to assess the systolic function of the mouse heart. Masson trichrome staining and Wheat germ agglutinin (WGA) staining were utilised to determine the fibrotic area and cross‐sectional area of the mouse heart, respectively. Cardiomyocytes and fibroblasts were isolated from neonatal rats aged 0–3 days in vitro using enzyme digestion. TUNEL staining and EdU staining were performed to evaluate apoptosis and proliferation, respectively. Gene expression changes were analysed by qRT–PCR, and protein expression changes were assessed by Western blotting. Our findings revealed that CRP attenuated cardiac hypertrophy, fibrosis and apoptosis and alleviated heart failure after MI in vivo. Furthermore, CRP mitigated cardiomyocyte apoptosis and fibroblast proliferation and differentiation into myofibroblasts. In addition, the PPARγ inhibitor T0070907 completely abolished the abovementioned beneficial effects of CRP, and the PPARγ activator rosiglitazone failed to further ameliorate cardiac apoptosis and fibrosis in vitro. CRP alleviates cardiac hypertrophy, fibrosis, and apoptosis and can ameliorate heart failure after MI via activation of PPARγ.